The effect of mindfulness-based counselling on the anxiety levels and childbirth satisfaction among primiparous pregnant women: a randomized controlled trial - Rozhin Feli; Sousan Heydarpour; Kamran Yazdanbakhsh; Fatemeh Heydarpour (BMC Psychiatry)
Abstract Background Anxiety during pregnancy is linked to adverse maternal and neonatal outcomes, as well as dissatisfaction with childbirth, and may contribute to the development of postpartum depression. This study aimed to evaluate the effect of mindfulness-based counselling on the anxiety levels and childbirth satisfaction among primiparous pregnant women. Methods This two-group, parallel, randomized controlled trial involved 60 eligible primiparous pregnant women who were referred to health centers in Kermanshah province (western Iran). Participants were selected based on inclusion/exclusion criteria and randomly assigned to either the experimental or control group using a simple randomization method. The control group (n = 30) received routine prenatal care, while the experimental group (n = 25) participated in eight group mindfulness-based counseling sessions (60–90 min each), held twice a week, in addition to routine prenatal care. The intervention was based on the Mindfulness-Based Childbirth and Parenting Program (MBCP), which aims to promote the health and well-being of families by integrating mindfulness practices throughout pregnancy, childbirth, and early parenthood. Both groups completed the Pregnancy-Related Anxiety Questionnaire (PRAQ) before, immediately after, and one month after the intervention. Additionally, 24 h post-delivery, both groups completed the Scales for Measuring Maternal Satisfaction in Normal and Caesarean Births (SMMS-normal and SMMS-caesarean). The scores were then compared. Recruitment took place between June and December 2019, and 55 participants completed the study. Data were analyzed using the Mann-Whitney U test, Independent t-test, and Friedman test with SPSS (25), and significance was set at p < 0.05. Results There was no significant difference between the control and experimental groups in terms of anxiety scores before the intervention. However, a significant difference was observed between the two groups immediately after the intervention (p = 0.001) and one month after (p = 0.001). In terms of childbirth satisfaction, the experimental group reported significantly higher satisfaction 24 h after delivery compared to the control group (p ≤ 0.001). No significant adverse events or side effects were reported. Conclusion The findings of this study suggest that mindfulness training for pregnant women can effectively reduce anxiety and enhance childbirth satisfaction. The 4-week Mindfulness-Based Childbirth and Parenting program for expectant mothers appears to be a well-received and effective intervention for improving maternal mental health. Trial registration Clinical Trials Iranian Registery of clinical trials-Beta version, https://en.irct.ir/trial/35390 (IRCT20170305032900N3), registered (2019-02-24).